2020
DOI: 10.1080/23311975.2020.1796249
|View full text |Cite
|
Sign up to set email alerts
|

Revisit intention and satisfaction: The role of destination image, perceived risk, and cultural contact

Abstract: This paper explores the relationship between destination image, cultural contact, perceived risk, satisfaction, and the revisit intention of international tourists to Binh Thuan province in Vietnam based on data obtained from 405 international tourists. Employing Partial Least Squares Structural Equation Modeling (PLS-SEM) techniques, the study delivered two key results. The first finding is that revisit intention is directly affected by satisfaction, attractiveness, accommodation service, cultural contact, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
62
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 87 publications
6
62
0
11
Order By: Relevance
“…These results are in line with and supported by several previous studies that explain the relationship between season index, experience quality, and revisit intention in different tourist destinations in several countries (Ramdhani and Astuti, 2019;Nguyen, 2020;Purnama and Wardi, 2019;Viet et al, 2020;Lin et al, 2018). This study has limitations on the number of samples, the survey period, and the variables used so that future researchers are expected to consider these three things so that the discussion is more varied.…”
Section: Discussionsupporting
confidence: 92%
“…These results are in line with and supported by several previous studies that explain the relationship between season index, experience quality, and revisit intention in different tourist destinations in several countries (Ramdhani and Astuti, 2019;Nguyen, 2020;Purnama and Wardi, 2019;Viet et al, 2020;Lin et al, 2018). This study has limitations on the number of samples, the survey period, and the variables used so that future researchers are expected to consider these three things so that the discussion is more varied.…”
Section: Discussionsupporting
confidence: 92%
“…This gives speculation that when visiting Singapore, tourists feel very comfortable and happy traveling from one place to another and make for a good and enjoyable tourist experience when visiting Singapore. In the tourism industry, the factors that influence tourists to revisit include satisfaction, attractiveness, accommodation, service, culture, risk [4]. [5] suggested that the factors that influence the intention of returning tourists include perceived behavioral control, perceived value, destination image and satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…terdapat enam faktor dalam persepsi risiko yang disebabkan oleh manusia yaitu keuangan, kualitas layanan, sosiopsikologis, bencana alam dan kecelakaan mobil serta masalah keamanan cuaca [13]. Wisatawan mungkin melihat masalah risiko secara berbeda karena variasi geografi, budaya, psikologi dan pengalaman perjalanan yang dapat mempengaruhi niat perilaku mereka dengan cara yang berbeda [15]. Terdapat tiga tipologi risiko yang paling relevan dengan kemungkinan wisatawan melakukan perjalanan wisata pasca pandemi Covid-19 yaitu kesehatan, psikologis dan resiko sosial [16].…”
Section: Pendahuluanunclassified
“…Hal ini sejalan dengan penelitian oleh beberapa ahli yang menyatakan bahwa perceived risk berpengaruh signifikan terhadap revisit intention [28]. Sedangkan hasil penelitian lain menyatakan bahwa perceived risk berpengaruh tidak signifikan terhadap revisit intention [13], [15]. Adanya pengaruh tidak signifikan disebabkan karena seseorang masih mempertimbangkan beberapa risiko yang mungkin mereka dapatkan ketika mengunjungi destinasi wisata seperti risiko kesehatan, keamanan dan keuangan.…”
Section: Pengaruh Perceived Risk Dengan Revisit Intentionunclassified
See 1 more Smart Citation